Accelerated MD Program Using CUDA Technology - Hue, Hoang Van; Ha, Nguyen Thi Thanh; Hung, Pham Khac (Communications in Physics, 2011)
Molecular dynamic (MD) simulation is proven to be an important tool to study the structure as well as the physical properties at atomic level in materials science. However, it requires a huge computing time and hence limits the ability to treat a large scale simulation. In this paper we present a solution to speed up the MD simulation using CUDA technology (Compute Unified Device Architecture). We used the GeForce GTS 250 card with Version 2.30. The simulation is implemented for Lennard-Jones systems with periodic boundary conditions which consist of 1024, 2048, 4096 and 8192 atoms. The calculation shows that the computing time depends on the size of system and could be decreased by 37 times. This result indicates a possibility of constructing a large MD model with up to 105 atoms on the usual PC.